2023
DOI: 10.1002/dad2.12482
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset Alzheimer's disease explained by polygenic risk of late‐onset disease?

William G. Mantyh,
J. Nicholas Cochran,
Jared W. Taylor
et al.

Abstract: Early‐onset Alzheimer's disease (AD) is highly heritable, yet only 10% of cases are associated with known pathogenic mutations. For early‐onset AD patients without an identified autosomal dominant cause, we hypothesized that their early‐onset disease reflects further enrichment of the common risk‐conferring single nucleotide polymorphisms associated with late‐onset AD.We applied a previously validated polygenic hazard score for late‐onset AD to 193 consecutive patients diagnosed at our tertiary dementia referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Overall, the transferability of a PRS derived from a LOAD population to an EOAD population is mixed, with some studies demonstrating poor correlation. 54,55 Other studies have shown a potential role of a LOAD-derived PRS in predicting EOAD cases, though differences in age of participants and APOE status may confound direct comparisons. [56][57][58][59] Our findings, along with those previously published, indicate the need for an EOAD-derived PRS, especially in individuals with non-familial cases.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the transferability of a PRS derived from a LOAD population to an EOAD population is mixed, with some studies demonstrating poor correlation. 54,55 Other studies have shown a potential role of a LOAD-derived PRS in predicting EOAD cases, though differences in age of participants and APOE status may confound direct comparisons. [56][57][58][59] Our findings, along with those previously published, indicate the need for an EOAD-derived PRS, especially in individuals with non-familial cases.…”
Section: Discussionmentioning
confidence: 99%
“…sEOAD have unveiled both common and rare variants in genes associated with LOAD, alongside novel variants, suggesting a partially overlapping genetic framework between sEOAD and LOAD [14][15][16] . Several genome-wide association studies (GWAS) have identified over 75 common variants linked to LOAD, with the APOE ε4 allele being the most significant genetic risk factor [17][18][19][20][21][22] .…”
mentioning
confidence: 99%